2020
DOI: 10.1002/alz.12005
|View full text |Cite
|
Sign up to set email alerts
|

PSEN1, PSEN2, and APP mutations in 404 Chinese pedigrees with familial Alzheimer's disease

Abstract: IntroductionThe PSENs/APP mutation distribution in Chinese patients with familial Alzheimer's disease (FAD) remains unclear. We aimed to analyze the genetic features of Chinese FAD pedigrees with and without PSENs/APP mutations.MethodsIn total, 1330 patients with Alzheimer's disease (AD) or mild cognitive impairment in 404 pedigrees were enrolled from the Chinese Familial Alzheimer's Disease Network. PSENs/APP mutations and APOE frequencies were determined.ResultsIn total, 13.12% of pedigrees carried PSENs/APP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 44 publications
1
53
2
1
Order By: Relevance
“…For instance, the CFAN discovered a lower detection rate of APP/PSEN mutations in the Chinese FAD population than that reported in Caucasians [45]. Additionally, it is also evident from the published studies that not all the susceptibility genes commonly found in Caucasian populations are present in Chinese AD patients [45,85]. For example, the CFAN reported a novel mutation in APP (M722K) in Chinese FAD patients, which was not found in other populations.…”
Section: Challenges and Future Insightsmentioning
confidence: 92%
See 4 more Smart Citations
“…For instance, the CFAN discovered a lower detection rate of APP/PSEN mutations in the Chinese FAD population than that reported in Caucasians [45]. Additionally, it is also evident from the published studies that not all the susceptibility genes commonly found in Caucasian populations are present in Chinese AD patients [45,85]. For example, the CFAN reported a novel mutation in APP (M722K) in Chinese FAD patients, which was not found in other populations.…”
Section: Challenges and Future Insightsmentioning
confidence: 92%
“…Besides, it is also of great value to compare the difference in genetic risk factors between Chinese population and other populations worldwide, as this may contribute to explain the heterogeneity in disease phenotypes and the development of specific treatments. For instance, the CFAN discovered a lower detection rate of APP/PSEN mutations in the Chinese FAD population than that reported in Caucasians [45]. Additionally, it is also evident from the published studies that not all the susceptibility genes commonly found in Caucasian populations are present in Chinese AD patients [45,85].…”
Section: Challenges and Future Insightsmentioning
confidence: 95%
See 3 more Smart Citations